2008
DOI: 10.1113/jphysiol.2008.153379
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore disassembly from endoplasmic reticulum membranes promotes Ca2+signalling competency

Abstract: The functionality of the endoplasmic reticulum (ER) as a Ca2+ storage organelle is supported by families of Ca 2+ pumps, buffers and channels that regulate Ca 2+ fluxes between the ER lumen and cytosol. Although many studies have identified heterogeneities in Ca 2+ fluxes throughout the ER, the question of how differential functionality of Ca 2+ channels is regulated within proximal regions of the same organelle is unresolved. Here, we studied the in vivo dynamics of an ER subdomain known as annulate lamellae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…On another hand, it is interesting to notice that in some cell types, NPC are also found in an ER subdomain known as annulate lamellae. It was recently found that IP 3 R activity is decreased within annulate lamellae and the relief of this inhibition is correlated with the dismantling of the NPC from this ER subdomain (Boulware and Marchant, 2008). It would be interesting to study whether NPC could also regulate Ca 2+ fluxes and IP 3 R activity within the NE.…”
Section: The Camentioning
confidence: 99%
“…On another hand, it is interesting to notice that in some cell types, NPC are also found in an ER subdomain known as annulate lamellae. It was recently found that IP 3 R activity is decreased within annulate lamellae and the relief of this inhibition is correlated with the dismantling of the NPC from this ER subdomain (Boulware and Marchant, 2008). It would be interesting to study whether NPC could also regulate Ca 2+ fluxes and IP 3 R activity within the NE.…”
Section: The Camentioning
confidence: 99%
“…For example, inositol (1,4,5)-trisphosphate [Ins(1,4,5)P 3 ]-dependent Ca 2+ release is sensitized during both meiosis (Fujiwara et al, 1993;Machaca, 2004) and mitosis (Malathi et al, 2003), and this sensitization depends on the cell-cycle kinase cascade (Lee et al, 2006;Lim et al, 2003;Sun et al, 2009). In addition, during the maturation of Xenopus oocytes, the number of functional Ins(1,4,5)P 3 receptors increases following their release from annulate lamellae, vesicular compartments in oocytes in which Ins(1,4,5)P 3 receptor function is suppressed (Boulware and Marchant, 2005;Boulware and Marchant, 2008). Furthermore, SOCE is inhibited both during Xenopus oocyte meiosis and during mammalian cell mitosis (Machaca and Haun, 2000;Preston et al, 1991).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…Boulware and Marchant (2008) sought ALPC function in the context of differential regulation of cytoplasmic Ca 2+ signaling. Their concept is based on the assumption that the numbers of ALPCs incorporated into reticulated cytoplasmic membranes affect the Ca 2+ stores.…”
Section: Resultsmentioning
confidence: 99%